2016
DOI: 10.1016/j.ygeno.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Focussing reduced representation CpG sequencing through judicious restriction enzyme choice

Abstract: Current restriction enzyme based reduced representation methylation analyses aim for limited, but unbiased, methylome coverage. As the current best estimate suggests that only ~20% of CpGs are dynamically regulated, we characterised the CpG and genomic context surrounding all suitable restriction enzyme sites to identify those that were located in regions rich in dynamically methylated CpGs. The restriction-site distributions for MspI, BstUI, and HhaI were non-random. CpGs in CGI and shelf+shore could be enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…HinP1 I (G ˇ CGC) sites as well as other methylation-sensitive restriction enzymes, such as Hpa II (C ˇ CGG), Hha I (GCG ˇ C), and BstU I (CG ˇ CG), are clustered in CpG islands. It has been reported that by using the 21 chromosomes of the mouse genome assembly (mm10, GRCm38, Dec2011 build UCSC), in silico prediction of enzymatically digested fragments revealed that Hpa II site and Hha I sites covered the most UCSC-annotated CpG island with 94.8 and 93.4%, respectively [ 14 ]. This indicates that the short HinP1 I- HinP1 I DNA fragments should be predominantly from in CpG islands.…”
Section: Resultsmentioning
confidence: 99%
“…HinP1 I (G ˇ CGC) sites as well as other methylation-sensitive restriction enzymes, such as Hpa II (C ˇ CGG), Hha I (GCG ˇ C), and BstU I (CG ˇ CG), are clustered in CpG islands. It has been reported that by using the 21 chromosomes of the mouse genome assembly (mm10, GRCm38, Dec2011 build UCSC), in silico prediction of enzymatically digested fragments revealed that Hpa II site and Hha I sites covered the most UCSC-annotated CpG island with 94.8 and 93.4%, respectively [ 14 ]. This indicates that the short HinP1 I- HinP1 I DNA fragments should be predominantly from in CpG islands.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have tested the potential of other restriction enzymes and enzyme combinations to expand the range of CpG sites that can be targeted in a genome ( 8 11 , 28 , 30 , 56 , 57 ). However, to our knowledge, there is currently no computational method that systematically explores the capacity of all commercially-available restriction enzymes to generate ‘personalised’ reduced-representations of the genome whilst minimising the experimental cost ( Supplementary Figure S2E ).…”
Section: Resultsmentioning
confidence: 99%
“…To address these cost inefficiencies, many methods have been developed to reduce the number of fragments that need to be sequenced for a given biological system or WGBS validation experiment ( 8 25 ). These methods can be broadly split into those that positively select for genomic fragments of interest and those that deplete for fragments that are not of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Fragments are then size-selected and sequenced to reveal the location of non-methylated sites [ 129 ]. However, since only around 20% of the CpG islands are dynamically regulated, MRE-sequencing lacks efficiency genome-wide and is more suited for specific loci [ 130 ]. A luminometric variation of this assay (LUMA: Luminometric Methylation Assay) has been used to show a decrease in global DNA methylation in both the PFC and amygdala following six months of peripheral nerve injury in mice [ 115 ].…”
Section: Dna Methylation and Painmentioning
confidence: 99%